SOCIODEMOGRAPHIC CHARACTERISTICS ASSOCIATED WITH ORAL HEALTH LITERACY IN ADULTS: A CROSS-SECTIONAL STUDY - Orozco-Vásquez, Sergio (2025)
Objective: To determine the sociodemographic characteristics associated with oral health literacy (OHL) in Peruvian adults attending a public health center in Lima. Materials and Methods: This cross-sectional study included 384 Peruvian adults aged 19 to 64 who visited a health center in Metropolitan Lima. OHL was measured using the Peruvian version of the Health Literacy in Dentistry-14 (HeLD-14) score. Sociodemographic characteristics, including gender, age, place of residence, number of children, health insurance status, educational level, occupation, and monthly income, were collected. Bivariate analysis was performed using the nonparametric Mann-Whitney U, Kruskal-Wallis, and Spearman correlation tests, while multivariate analysis was conducted using the linear regression model with a significance level of 5%. Results: The average OHL score was 48.60 ± 6.89. Literacy was higher in women (p = 0.004) and among those with higher incomes (p = 0.002). Conversely, literacy decreased with increasing age (p = 0.022) and number of children (p = 0.033). In the adjusted model, an association was found with being female (β = 0.097, p = 0.001), younger age (β = -0.003, p = 0.015), and a monthly income greater than five minimum wages (β = 0.100, p = 0.025). Conclusion: OHL in an adult population in an urban area tends to be high and is associated with sociodemographic characteristics such as gender, age, and monthly income.